Práticas de numeramento na formação inicial de pedagogos - Rodrigues, Rosimeire Aparecida (2020)
The research consists of a study on the initial training of teachers who will teach mathematics for the early years of elementary school, mediated by numeracy practices in the appropriation of knowledge from and for teaching, with a undergraduate students group of Pedagogy course at the Universidade Federal de Tocantins. The question that configured the research problem was: What teaching learnings are mobilized by a group of undergraduate students in Pedagogy, based on numeracy practices experienced in an extension-training course? In the search for answers, at first, theories on teacher training, numbering and their practices were resumed, following the precepts of: Freixo (2010), Pimenta (2002, 2012), Fiorentini (1995, 2005), Josso (2004, 2008), Pereira (2013), Fonseca (2004, 2005, 2007, 2012), Mendes (2001, 2004, 2007), Street (1984, 2003, 2014), Neill (2001), Shulman (1987, 2014) and Mizukami (2004). Then, a training proposal is presented with students from the Pedagogy course developed and analyzed from the perspective of numbering practices (carried out in partnership with two school institutions in the municipality of Arraias-TO) and of conceptions about the appropriation of knowledge teachers. With this, the objective was to understand what learning from/for teaching the undergraduate Pedagogy graduates mobilize, from the study and the experience of numeracy practices in an extension-training course. The research had as sources and instruments of data production: questionnaires (diagnostic and evaluative); group meeting records; graduates' training memorials; records of the licensee's numeracy practices; and, field diaries of the graduates and the researcher. From the reading and systematization of the data, three axes of analysis emerged: I. school experiences, concepts of learning and teaching mathematics, and the expectations of the undergraduate students; II. learnings of teaching by numeracy practices; and, III. the interactions between the different training spaces. The results indicate that: through the extension-training course, the undergraduate students (re)constituted the learnings of the teaching knowledge about the mathematics teaching; the reflections on the practices carried out provided opportunities for new ways of seeing and thinking about the training itself; and, the mathematical concepts of the undergraduate students were (re)elaborated during the development of the numeracy proposals - experienced at school and expanded in the formative moments with the group. The practices developed enabled learnings from and for teaching: in the appropriation of mathematical knowledges in line with the specificities of the use of numerical thinking and quantities; in the didactic and methodological confrontations of teaching practice in proposing numeracy events; in the conscious mobilization of the use of numerical thinking and quantities; and, in the (re)knowledge of the content domain in numerical relations and the operational process. In addition, the lived experiences in and with the group contributed with learning to teach, favoring: the learning about teaching strategies; the understanding the importance of contextualization and interaction in the relationships and correlations of the contents; the integration of curricular content into everyday life, giving it senses and meanings; the facing personal, conceptual and pedagogical challenges; and, the teaching knowledge of /about the mathematics teaching and learning process in the early years scholl.